1998
DOI: 10.1523/jneurosci.18-03-00987.1998
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Kinase Expression and Localization in Growth Cone Migration

Abstract: Migrating neuronal growth cones exert traction forces that are generated by ATP-driven F-actin/myosin interactions. Sustained generation of these forces may require an energy supply mediated by the guanidino kinases, creatine kinase and arginine kinase. We cloned and sequenced grasshopper arginine kinase and examined its expression during embryogenesis and its subcellular localization in vivo and in vitro. During the first half of embryogenesis, arginine kinase is expressed selectively in a small percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 75 publications
1
28
0
1
Order By: Relevance
“…This difference in vulnerability of the brain is also found clinically, because hyperammonemia causes irreversible CNS symptoms compatible with axonal loss in neonates and infants but not in adults (Brusilow and Horwich, 2001). Evidence for direct coupling of the Cr/PCr/CK system to growth cone activity and axonal growth (Wang et al, 1998) and Cr and PCr age dependency of the CNS in the first weeks of postnatal life (Tsuji et al, 1995) also supports the difference we found between developing and mature aggregates. It suggests a higher CNS sensitivity to Cr variations in young children than in adulthood.…”
Section: Nh 4 CL Exposure Does Not Alter Axonal Morphology In Mature supporting
confidence: 85%
See 1 more Smart Citation
“…This difference in vulnerability of the brain is also found clinically, because hyperammonemia causes irreversible CNS symptoms compatible with axonal loss in neonates and infants but not in adults (Brusilow and Horwich, 2001). Evidence for direct coupling of the Cr/PCr/CK system to growth cone activity and axonal growth (Wang et al, 1998) and Cr and PCr age dependency of the CNS in the first weeks of postnatal life (Tsuji et al, 1995) also supports the difference we found between developing and mature aggregates. It suggests a higher CNS sensitivity to Cr variations in young children than in adulthood.…”
Section: Nh 4 CL Exposure Does Not Alter Axonal Morphology In Mature supporting
confidence: 85%
“…There is substantial evidence that creatine (Cr) and the Cr/phosphocreatine (PCr)/creatine kinase (CK) system are involved in neuronal growth cone activity and axonal elongation (Wang et al, 1998). In addition, the CNS is the main affected target in infants with a creatine deficiency syndrome attributable to guanidinoacetate methyltransferase, arginine:glycine amidinotransferase, or Cr transporter deficiencies.…”
mentioning
confidence: 99%
“…The literature on phosphoenolpyruvate phosphomutase is scarce and its possible involvement in DUI unclear. Of the proteins with multiple occurrences, arginine kinase is a phosphotransferase involved in supplying ATP to cellular processes including growth and motility (79). It has been reported in sea-urchin Paracentrotus lividus eggs (80) and high levels observed during oocyte development of a penaeid shrimp suggests an important role in meeting energy demands for cell growth and proliferation (81).…”
Section: Discussionmentioning
confidence: 99%
“…The cytosolic muscle isoform localizes along the M-line to the myosin heads where it provides ATP during actomyosin contraction (24). The cytosolic brain isoform (CKB) and its insect homolog arginine kinase localize to the membranes of neurons and astrocytes and are concentrated along axons and moving lamellipodial edges of migrating glia, although the precise function of CKB is not known (25,26).We hypothesized that molecules necessary for the early stages of thrombin signaling might bind to the intracellular face of PAR-1. To examine this, we performed a yeast two-hybrid screen and discovered an interaction between the PAR-1 cytoplasmic tail (C-tail) and CKB.…”
mentioning
confidence: 99%
“…To examine this, we performed a yeast two-hybrid screen and discovered an interaction between the PAR-1 cytoplasmic tail (C-tail) and CKB. Because the muscle isoform of creatine kinase delivers a burst of compartmentalized ATP for contracting skeletal muscle and is linked to actomyosin function in various cells (22,26,27), we hypothesized that CKB may perform a similar function during PAR-1-directed cytoskeletal reorganization. Using three different methods to ablate CKB activity, we found that CKB was necessary for PAR-1 signal transduction to the cytoskeleton.…”
mentioning
confidence: 99%